Strategic communication and barriers to strategy implementation - Pereira, L.; Durão, T.; Santos, J. (2019 IEEE International Conference on Engineering, Technology and Innovation (ICE/ITMC), 2019)
This research work's core objective is to categorise and understand the barriers to strategic implementation, focusing, then, through an inquiry, in the most voted of them, to make a deeper analysis on one of the variables. To that end, this document begins with a literature review and begins to identify the importance that strategic communication has in the process of propagating a given individual idea or, in the terms that interests us most, within of an organization - whether ascending or descending, horizontal or vertical. In the organizational arena, business and communication are two inseparable issues.Then it is explained more deeply in what barriers to strategic implementation consists, in its variances of application and how it is immersed in the multiple possibilities that can cause the collapse of the plans orchestrated by the companies. In the end, as a theoretical complement, a questionnaire was designed for a relatively large number of people who were confronted with the topics under discussion throughout this article.